The Implementation of Canva-Assisted Flipped Classroom Model to Improve Mathematics Learning Outcomes - Yasin, Ma'ruf; Badu, Syamsu Qamar; Irfah, Auli (IKIP Siliwangi, 2025)
This study is motivated by the importance of utilizing innovative teaching models to improve students' mathematics learning outcomes. One such model is the Flipped Classroom, supported by interactive media like Canva. The purpose of this study is to determine the difference in mathematics learning outcomes between students taught using the Flipped Classroom model assisted by Canva interactive media and those taught using the direct instruction model with the same media. The research method used is experimental, employing a Post-test only control group design. Cluster random sampling was used for sampling. The instrument used was a learning outcome test in the form of an essay (post-test). Hypothesis testing was conducted using a t-test, which resulted in a t_calculated value of 2.59, while the t_table value with 60 degrees of freedom at a 0.05 significance level was lower. By comparing these values, the null hypothesis was rejected, and the alternative hypothesis was accepted. Additionally, the calculation of the effect size using Cohen’s d formula yielded a value of 0.66, indicating a medium effect. In conclusion, the use of the Flipped Classroom model assisted by Canva interactive media not only resulted in a statistically significant difference but also had a moderate practical effect on improving students' mathematics learning outcomes.